Digital video passive forensics for its authenticity and source - CHEN Wei-bing1; YANG Gao-bo2; CHEN Ri-chao2; ZHU Ning-bo2 (Tongxin xuebao)
The characteristics of various video forgery operations and their influences to video passive forensics were analyzed.From two aspects of authenticity and source identifications,typical approaches in passive video forensics,such as those video forgery trails-based and video capturing device-based techniques,are summarized.The main problems ex-iting in current research field and some urgent topics for future research are also investigated in detail.